The role of farmers' intrinsic motivation in the effectiveness of policy incentives to promote sustainable agricultural practices. (15th August 2019) - Bopp, Carlos; Engler, Alejandra; Poortvliet, P. Marijn; Jara-Rojas, Roberto
Abstract: This paper examines the effectiveness of intrinsic and extrinsic motivations on the adoption intensity of sustainable agricultural practices (SAPs) among annual crop farmers in Chile. We use the farmers' attitude towards SAPs as a proxy of intrinsic motivation, while extrinsic motivation is represented by an economic incentive to promote the use of SAPs. The policy program we studied is administered by the Chilean Ministry of Agriculture under the name System of Incentives for the Agro-Environmental Sustainability of Degraded Soils (SIRSD-S. Sustainable behaviour was defined as the adoption of (1) minimum tillage, (2) improved fallow, (3) stubble incorporation, (4) use of manure, and (5) use of compost. A count model was estimated that showed that both sources of motivation, and the interaction between them, significantly predicted the adoption of SAPs. Farmers with low levels of intrinsic motivation depended largely on the SIRSD-S to adopt SAPs, while the incentive was ineffective for intrinsically motivated farmers who adopted more SAPs regardless the presence of extrinsic motivation. Finally, the perception of risk of soil erosion and perceived behavioural control of this risk were found to play a positive role in the adoption of SAPs. Highlights: A motivational model of sustainable behavior is estimated at the farm level. Sustainable behaviour is driven by intrinsic and extrinsic motivations. Motivations interact negatively, lessening one's effects as the other increases. A monetary incentive does not affect behaviour when intrinsic motivation is high. Risk perception and perceived behavioural control foster sustainable agriculture.